Improvement of the standard device for entering a gas-liquid mixture into a gas separator - Shestakova Evgenya; Bulyukova Flura; Zainagalina Liaisan; Davydov Alexander; Zaylalova Venera (E3S Web of Conferences)
The paper provides a literature review and patent study on the topic of the gas separator. It is revealed that the largest amount of information falls on the gas-liquid flow input devices. It has been established that improving the gas-liquid mixture injection device for pre-separation of liquid from gas is an urgent task to prevent liquid entrainment and increase separation efficiency. Various designs of the gas-liquid mixture injection device have been studied. It was revealed that the blade flow distributor of the IVC "Injekhim" company is suitable for the tasks of the work. The choice of the device is justified using mathematical calculations and computer modeling. It is proved that the reduction in the velocity of the gas-liquid mixture is about 40% of the average inlet velocity, which meets the stated requirements for the operation of the input devices.